Mediation as a value and chance for Ukraine. - Patsurkivskyy, Petro; Havrylyuk, Ruslana (My University, 2021)
In the article mediation as a qualitatively isolated self-sufficient value (culture) o f a developed civil society is investigated from the standpoint o f anthroposociocultural approach. It is substantiated that the quintessence o f mediation is the preservation and protection o f human dignity in resolving conflicts by their participants with the assistance ofprofessional medi ators, as well as revealed the basic principles o f mediation - human-centrism, denial o f violent orders in society and paternalism. It is proved that mediation has a complex nature — it is dialogical, it exists as both a public good and a social service, it is a form of freedom, justice and social partnership, and the attributes o f mediation are the trust o f the conflicting parties to each other and social optimism. It is substantiated conclusions that: a) the assertion o f mediation as a value (culture o f mediation) in society is a real Copernican revolution in public views on methods o f conflict resolution and one o f the most important manifestations o f the subjectivity o f the individual; b) mediation belongs to paradigm atically opposite values in comparison with the values o f state j u diciary; c) mediation embodies the postmodern way o f being and thinking, and therefore can be adequately perceived through the corresponding categorical-conceptual apparatus o f non-classical standards o f science, from the worldview and methodological approaches o f postmodernism.
Keywords: mediation; udiciary; value; value matrix of mediation; value matrix ofjudiciary; anthroposociocultural code o f mediation; sociocultural code of judiciary